THE INFLUENCE OF ADVERTISING FREQUENCY ON CONSUMER PURCHASE INTENTION OF YOUTUBE PLATFORM THROUGH BRAND AWARENESS AND BRAND TRUST AS INTERVINING VARIABLES - Fina Rabya Syabina Kusuma; Finnah Fourqoniah; Annisa Wahyuni Arsyad; Poppy Alvianolita Anistasya (Universitas Tulungagung, 2025)
This study examines the influence of YouTube advertising frequency on consumer purchase intention for Traveloka, mediated by brand awareness and brand trust. With Indonesia’s internet penetration reaching 79.5% and YouTube attracting over 139 million users, digital platforms have become central to marketing strategies. Traveloka, the most visited online travel agent in Indonesia, leverages YouTube ads to enhance consumer engagement. Using a quantitative approach, 164 purposively sampled respondents who had been exposed to Traveloka’s YouTube advertisements were surveyed. Data were analyzed using SEM-PLS to assess measurement and structural models. Results indicate that advertising frequency significantly increases both brand awareness and brand trust, with brand trust exerting a stronger effect on purchase intention. Specifically, advertising frequency showed moderate effects on brand awareness (f²=0.319) and brand trust (f²=0.343), while brand trust had a large effect on purchase intention (f²=0.452) compared to brand awareness’s small effect (f²=0.231). R² values revealed that brand awareness and trust jointly explained 70.4% of purchase intention variance. All hypothesized relationships were statistically significant (p<0.05). The study concludes that optimal ad frequency fosters trust and awareness, enhancing purchase intentions, and recommends maintaining ad consistency while avoiding consumer fatigue. Future research should incorporate additional variables such as brand image, e-WOM, and customer satisfaction, alongside broader demographic sampling to improve generalizability.